2022
DOI: 10.1128/aem.02149-21
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Epidemiology of Salmonella enterica Circulating in Surface Waters Used in Agriculture and Aquaculture in Central Mexico

Abstract: Salmonella enterica (SE) can survive in surface waters (SuWa) and the role of non-host environments in its transmission has acquired increasing relevance. In this study, we conducted comparative genomic analyses of 172 SE isolates collected from SuWa across three months in six states of central Mexico during 2019. SE transmission dynamics were assessed using 87 experimental and 112 public isolates from Mexico collected during 2002-2019. We also studied genetic relatedness between SuWa isolates and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…This sequence type has been identified in healthy cattle isolated from fecal samples and lymph nodes [48]. Salmonella Give ST 654 has been isolated from surface water used for aquaculture and crop production in Mexico, along with serovars Meleagridis, Newport, and Anatum [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This sequence type has been identified in healthy cattle isolated from fecal samples and lymph nodes [48]. Salmonella Give ST 654 has been isolated from surface water used for aquaculture and crop production in Mexico, along with serovars Meleagridis, Newport, and Anatum [18].…”
Section: Discussionmentioning
confidence: 99%
“…In Mexico, there is little information about the prevalence of Salmonella enterica in apparently healthy cattle and farm environments, the diversity of serovars associated with livestock, and the presence of antimicrobial resistance and virulence genes [17,18]. Therefore, the objectives of this study were to determine the prevalence of Salmonella enterica in dairy systems, examine the serovars and sequence types, and evaluate the presence of virulence and antimicrobial resistance genes circulating in 13 states of Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…According to the SNP phylogenetic analysis conducted in the present study, S. enterica isolates belonging to same serovar clustered together by MLST and had similar phylogenies according to the analysis of core genome SNPs and highly variable SNPs. Recently, a report on S. enterica isolates recovered from surface waters in central Mexico identified significantly higher intraserovar diversity based on the CSIPhylogeny analysis of highly variable SNPs [23]. Moreover, SNP phylogeny identified that some isolates belonging to the same serovar were grouped in different SNP clusters [23].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a report on S. enterica isolates recovered from surface waters in central Mexico identified significantly higher intraserovar diversity based on the CSIPhylogeny analysis of highly variable SNPs [23]. Moreover, SNP phylogeny identified that some isolates belonging to the same serovar were grouped in different SNP clusters [23]. By contrast, the S. enterica isolates from river water in the Culiacan Valley in northwestern Mexico were closely related with lower intraserovar diversity and were found to have less than 400 SNP if they belonged to the same serovar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation